MicroRNA-146a Is a Wide-Reaching Neuroinflammatory Regulator and Potential Treatment Target in Neurological Diseases - Fan, Weihao; Liang, Chunmei; Ou, Mingqian; Zou, Ting; Sun, Furong; Zhou, Haihong; Cui, Lili (Frontiers in Molecular Neuroscience, 2020)
Progressive functional deterioration and loss of neurons underlies neurological diseases and constitutes an important cause of disability and death worldwide. The causes of various types of neurological diseases often share several critical nerve-related cellular mechanisms and pathological features, particularly the neuroinflammatory response in the nervous system. A rapidly growing body of evidence indicates that various microRNAs play pivotal roles in these processes in neurological diseases and might be viable therapeutic targets. Among these microRNAs, microRNA-146a (miR-146a) stands out due to the rapid increase in recent literature on its mechanistic involvement in neurological diseases. In this review, we summarize and highlight the critical role of miR-146a in neurological diseases. MiR-146a polymorphisms are associated with the risk of neurological disease. Alterations in miR-146a expression levels are crucial events in the pathogenesis of numerous neurological diseases that are spatially and temporally diverse. Additionally, the target genes of miR-146a are involved in the regulation of pathophysiological processes in neurological diseases, particularly the neuroinflammatory response. In summary, miR-146a mainly plays a critical role in neuroinflammation during the progression of neurological diseases and might be a prospective biomarker and therapeutic target. Understanding the mechanisms by which miR-146a affects the neuroinflammatory response in different neurological injuries, different cell types, and even different stages of certain neurological diseases will pave the way for its use as a therapeutic target in neurodegenerative diseases.